2014
DOI: 10.1155/2014/340257
|View full text |Cite
|
Sign up to set email alerts
|

Management of Fibrosis: The Mesenchymal Stromal Cells Breakthrough

Abstract: Fibrosis is the endpoint of many chronic inflammatory diseases and is defined by an abnormal accumulation of extracellular matrix components. Despite its slow progression, it leads to organ malfunction. Fibrosis can affect almost any tissue. Due to its high frequency, in particular in the heart, lungs, liver, and kidneys, many studies have been conducted to find satisfactory treatments. Despite these efforts, current fibrosis management therapies either are insufficiently effective or induce severe adverse eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 123 publications
(225 reference statements)
7
106
0
6
Order By: Relevance
“…Around 30 clinical trials are currently registered worldwide for evaluating MSC therapy for fibrosis [45]. Furthermore, a first-in-human clinical trial of FM-MSC transplantation in nine patients with steroid-refractory acute graft-versus-host disease (GVHD) demonstrated that the use of FM-MSCs appeared safe for intravenous infusion and the overall response rate in severe refractory acute GVHD was similar to the rate observed by using bone marrow-derived MSCs [42].…”
Section: Discussionmentioning
confidence: 99%
“…Around 30 clinical trials are currently registered worldwide for evaluating MSC therapy for fibrosis [45]. Furthermore, a first-in-human clinical trial of FM-MSC transplantation in nine patients with steroid-refractory acute graft-versus-host disease (GVHD) demonstrated that the use of FM-MSCs appeared safe for intravenous infusion and the overall response rate in severe refractory acute GVHD was similar to the rate observed by using bone marrow-derived MSCs [42].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an effective treatment strategy for RILI is urgently required. Development of RILI is a complex and continuous process, which is pathologically divided into two phases: the early pneumonitis phase and the later fibrosis phase [4]. Considerable inflammation in early pneumonitis and restricted breathing in later fibrosis make it difficult to treat RILI.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, BMSCs have been used to treat various diseases and have been shown to improve hepatic fibrosis to some extent (Usunier et al, 2014). Studies have shown that six-months after an intravenous injection of cultured BMSCs, patients' liver function indexes, pathological results of hepatic tissue and color Doppler ultrasound were improved, indicating the safety and effectiveness of BMSCs for treating cirrhosis (Mohamadnejad et al, 2007).…”
Section: Discussionmentioning
confidence: 99%